2014
DOI: 10.1128/jcm.01135-14
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Commercially Developed Semiautomated PCR–Surface-Enhanced Raman Scattering Assay for Diagnosis of Invasive Fungal Disease

Abstract: c Nonculture-based tests are gaining popularity in the diagnosis of invasive fungal disease (IFD), but PCR is excluded from disease-defining criteria because of limited standardization and a lack of commercial assays. Commercial PCR assays may have a standardized methodology while providing quality assurance. The detection of PCR products by a surface-enhanced Raman scattering (SERS) assay potentially provides superior analytical sensitivity and multiplexing capacity compared to that of realtime PCR. Using thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 22 publications
1
26
0
Order By: Relevance
“…Meta-analysis of results for various PCR-based methods for detection of candidaemia has concluded that PCR has very high sensitivity of 95% 6. We found the test’s specificity to be high, similar to that reported previously 12. The relatively lower sensitivity in this study may be explained by both the small case number and retrospective testing.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Meta-analysis of results for various PCR-based methods for detection of candidaemia has concluded that PCR has very high sensitivity of 95% 6. We found the test’s specificity to be high, similar to that reported previously 12. The relatively lower sensitivity in this study may be explained by both the small case number and retrospective testing.…”
Section: Discussionsupporting
confidence: 87%
“…The RenDx PCR test has previously been validated in a study of 93 blood specimens spiked with Aspergillus or Candida as well as blood samples from 112 high-risk patients, of whom seven had candidaemia; all seven were positive with the RenDx test 12. By comparison, another commercially available Candida PCR test (from T2 Biosystems) has been validated using 300 spiked blood specimens as well as blood samples from a large patient cohort, of which six had documented candidaemia; four of these were detected by the T2 assay 14…”
Section: Discussionmentioning
confidence: 99%
“…163 SERRS uses sensors that detect light scattered through the production of PCR-amplified DNA, in conjunction with a specific dye placed against a roughened surface such as gold or silver. 164 There was a 95% limit of detection of Candida and Aspergillus of 200 copies/reaction with overall reproducibility of 92.1%. A new platform, the RenDx (Renishaw Diagnostics, UK), was developed for detection of nucleic acid targets by Raman spectroscopy, including multiplex detection of up to 10 targets per reaction.…”
Section: Combined Proteomic-genomic Approachesmentioning
confidence: 95%
“…While SERS-tags have evolved into regulatory approved clinical assays, 178 the de novo identification of biomolecules is quickly catching up. De novo SERS detection described above indicates that a number of factors are important for SERS identification and quantification.…”
Section: Summary and Future Outlookmentioning
confidence: 99%